Genome-centric investigation of bile acid-metabolizing microbiota in chickens and their association with Eimeria tenella and Salmonella typhimurium infections - Shang, Kai-Meng; Elsheikha, Hany M.; Wei, Yong-Jie; Zhang, Xiao-Xuan; Hou, Xin-Wen; Yu, Hai-Long; Cai, Yanan; Ni, Hong-Bo; Liu, Rui; Ma, He; Jiang, Jing; Nan, Fulong; et al. (Frontiers in Veterinary Science, 2025)
IntroductionBile acid (BA) metabolism by gut microbiota plays a crucial role in host health by influencing nutrient absorption, immune responses, and resistance to pathogens. Elucidating how enteric infections disrupt the BA-microbiota axis is crucial for advancing microbiota-based therapeutics, precision nutrition, and post-antibiotic disease control strategies.MethodsWe reconstructed 9,990 high-quality microbial genomes from the gut microbiota of chicken and performed genome-resolved metabolic profiling. Comparative analyses were conducted across host species, including humans and pigs. Also, 135 intestinal samples collected from different regions of the chicken gut were analyzed. Additional samples from chickens infected with Salmonella typhimurium and Eimeria tenella were included to assess infection-associated alterations.ResultsOur results reveal that the phylum Bacillota_A is predominant, with key BA-transforming enzymes, including bile salt hydrolase (BSH) and 7α-hydroxysteroid dehydrogenase (7α-HSDH), present in a substantial proportion of the genomes. Chickens harbored a higher proportion of BSH genes compared to humans and pigs, with Ligilactobacillus and Alistipes identified as major contributors. Region-specific analysis showed that BA-metabolizing microbes are unevenly distributed along the intestinal tract, with the highest diversity observed in the cecum and colon. Experimental pathogen challenges revealed that S. typhimurium infection altered BSH gene abundance and overall microbial community structure, whereas E. tenella infection increased taxonomic richness but reduced community evenness.DiscussionTogether, these findings advance our understanding of microbial contributions to BA dynamics in poultry and offer insights into the role of BA metabolism in gut health and pathogen resistance.